Multinationality and downside risk: The roles of option portfolio and organization - Belderbos, René; Tong, Tony W.; Wu, Shubin (Strategic Management Journal, 2014)
Multinational operations confer firms a portfolio of switching options that offer potential operating flexibility in the context of input cost variability, helping firms reduce downside risk. We suggest that two conditions may shape the relationship between multinationality and downside risk. When subadditivity is present in a firm's option portfolio, such as when the firm operates affiliates in host countries with similar labor cost developments, multinationality is less likely to reduce downside risk since less valuable opportunities exist for shifting operations. Multinationality is more likely to reduce downside risk if a firm's organization facilitates the coordination of cross‐border activities, enabling the exploitation of the shifting opportunities. Analysis of a comprehensive panel dataset of Japanese manufacturing firms and their foreign manufacturing affiliates provides support for these conjectures . Copyright © 2013 John Wiley & Sons, Ltd.